Intraocular Pressure of Premature Newborns - A 2 Year Follow up - Kiril Slaveykov; Kalina Trifonova; Hristo Mumdzhiev (Mashhad University of Medical Sciences, 2024)
Background: The intraocular pressure (IOP) ranges of premature newborns are not the same as those in full-term newborns and adult population. There are no unified standards for IOP in infants, much less premature newborn. Research on the topic is very conflicting and needs to be expanded upon. To assess IOP in premature and full-term newborns and factors influencing it. Methods: Using a hand-held rebound tonometer, IOP was measured in 548 eyes of 274 preterm infants (gestational age ranging from 26 to 32 weeks) shortly after birth and at weekly intervals for one month. Results: The mean gestational age for premature newborns was 30.23±2.34 weeks (25-35 weeks), for full-term newborn it was 39.19±0.91 weeks (37-41 weeks). Mean IOP values in preterm infants were 21.95±4.36 mmHg (ranging from 11.1 to 32 mmHg), while for full-term were 13.5±2.9 (from 10.5 to 25.1 mmHg). At the end of the first month the mean IOP decreased to 17.66 ± 2.21 mm Hg (P < .001) for preterm newborns, while not changing in a statistically significant way for the full-term ones (P>0.5). Central corneal thickness was found to be among the major factors associated with increased IOP (P<.001). Conclusion: Measured values of IOP are well outside the normal range for newborns. There is a tendency for decreasing IOP observed during the first month screening which decreases the value of the initial findings. The exact causes of the decrease of IOP are not completely clear up to this point. Use of eyelid speculum needs to be avoided to prevent artificial increase of IOP.